La rue du chat-qui-pêche - Földes, Jolán; Van Moppès, Denise; Masereel, Frans (Gand : Snoeck-Ducaju, 1947)
Bibliotheek Jan Baghus
Genummerd exemplaar 499, met handtekening van Frans Masereel
Frans
Monografie